Chondro-Osseous Respiratory Epithelial Adenomatoid Hamartoma of the Skull Base: Report of a Case and Literature Review - Trent, Monica S.; Wang, Beverly; Kuan, Edward C. (Journal of Neurological Surgery Reports, 2025)
Chondro-osseous respiratory epithelial adenomatoid hamartoma (COREAH) is a rare benign growth within the nasal cavity or paranasal sinuses. We aim to highlight the pathogenesis and clinical presentation of an extremely rare benign mass within the nasal cavity and demonstrate the workup, diagnosis, and management of this rare lesion, as well as review the literature.Retrospective review of a patient presenting with COREAH of the sinonasal cavity treated at a single tertiary academic medical center. The MEDLINE database was additionally searched for all case series or reports of sinonasal or skull base COREAH.A total of sixteen articles were identified for review. In addition to the current case, a total of nineteen patients were identified in literature found to have sinonasal or skull base COREAH. The most common primary sites of attachment were the lateral nasal wall and posterior septum. Only two cases were identified with skull base attachment. Computed topography (CT) was employed in 84.2% of patients, and CT with MRI was utilized in 26.3% of patients. Endoscopic resection was performed in 100% of patients, with one recurrence reported in the literature and one incomplete resection requiring revision surgery.COREAH is an extremely rare hamartoma consisting of glandular proliferation with cartilaginous and osseous stroma. COREAH is symptomatic in 100% of reported cases in the literature, and complete surgical resection is often curative. Our case represents the longest follow-up reported with 4 years postoperatively revealing no growth or recurrence of COREAH.
Keywords: COREAH; chondro-osseous respiratory epithelial adenomatoid hamartoma; sinonasal mass